Simplify the expression. Assume all variables are positive.

( 3sqrt x times sqrt x^5 )/sqrt(25x^16)

the 3 is in the root. sqrt stands for the square root sign. x is variable.

### 1 Answer | Add Yours

`(^3sqrt(x) sqrt(x^5))/sqrt(25x^16) `

`(x^(1/3)(x^(5/2)))/(5x^8)`

`x^(1/3+5/2) / (5x^8)`

`==> (x^(17/6))/(5x^8)`

`==> (1/5) x^(17/6 - 8)`

`==> (1/5)x^(-31/6)`

`==> 1/(5x^(31/6))`

`==> 1/(5 x^(30/6) x^(1/6))`

`==> 1/(5x^5 x^(1/6))`

`==> 1/(5x^5 (^6sqrt x))`

``

``

``

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes